THE ROLE OF WORK SAFETY SCORECARD IN DETERMINING AND IMPROVING HEALTH, SAFETY AND ENVIRONMENTAL PERFORMANCE (A case study of Hearts and Minds program implementation in PT. Merck Sharp and Dohme tbk) - Wasis Purnomo (Jurnal Administrasi Bisnis, 2015)
This study aims to determine whether the existing Health, Safety and Environmental (HSE) Scorecard - Hearts and Minds Programme - function well in assessing the HSE performance as well as finding solutions to the problems that faced by the company. The type of research used in this study is a descriptive study with qualitative approach. Data was collected at PT. Merck Sharp & Dohme Tbk through interviews with the head and assistant of HSE Department, also distributing questionnaires to 13 reperesentative (supervisors or managers) of each departments in the company as data support. Based on the analysis using a guide from Hearts and Minds Programme on the interview, data showed that the company is at the Calcluative level which Hudson stated that the company can be describe as having a good HSE performance when they are at this level and advised to leaves the regulatory drive behind for company that already on this level. The researcher discover another thing from the analysis of supporting data that obtained which showed despite of all aspects of the company aggregated at the level of calculative, some departments are still far below the calculative level. Keyword : Health Safety and Environmental (HSE), Scorecard, Hearts and Minds Programme, Calculative level ABSTRAK Penelitian ini bertujuan untuk mengetahui apakah health, safety and environmental (HSE) scorecard perusahaan yang telah tersedia – hearts and minds programme – berfungsi dengan baik dalam menilai performa HSE serta mencari solusi terhadap masalah yang dihadapi oleh perusahaan. Jenis penelitian yang digunakan adalah penelitian descriptive dengan pendekatan kualitatif. Data diperoleh dari PT. Merck Sharp & Dohme Tbk melalui wawancara dengan ketua dan asisten di Departemen HSE, serta penyebaran kuesioner berdasarkan 13 representasi dari setiap departemen yang ada di perusahaan sebagai data pendukung. Berdasarkan hasil uji analisis menggunakan panduan hearts and minds programme diperoleh hasil bahwa dari data wawancara, perusahaan berada pada level calcluative. Hudson menyatakan, bahwa perusahaan dapat dikatakan baik ketika mereka sudah berada pada level ini dan mampu menyarankan untuk berhenti mengatur karyawan melalui peraturan tertulis. Namun, dari data pendukung yang diperoleh menunjukkan meskipun dari keseluruhan aspek perusahaan ketika dirata rata berada pada level calculative, beberapa departemen masih berada jauh dibawah level calculative. Kata Kunci : Health Safety and Environmental (HSE), Scorecard, Hearts and Minds Programme, level Calculative